Major loss of coralline algal diversity in response to ocean acidification. (16th July 2021) - Peña, Viviana; Harvey, Ben P.; Agostini, Sylvain; Porzio, Lucia; Milazzo, Marco; Horta, Paulo; Le Gall, Line; Hall‐Spencer, Jason M.
Abstract: Calcified coralline algae are ecologically important in rocky habitats in the marine photic zone worldwide and there is growing concern that ocean acidification will severely impact them. Laboratory studies of these algae in simulated ocean acidification conditions have revealed wide variability in growth, photosynthesis and calcification responses, making it difficult to assess their future biodiversity, abundance and contribution to ecosystem function. Here, we apply molecular systematic tools to assess the impact of natural gradients in seawater carbonate chemistry on the biodiversity of coralline algae in the Mediterranean and the NW Pacific, link this to their evolutionary history and evaluate their potential future biodiversity and abundance. We found a decrease in the taxonomic diversity of coralline algae with increasing acidification with more than half of the species lost in high p CO2 conditions. Sporolithales is the oldest order (Lower Cretaceous) and diversified when ocean chemistry favoured low Mg calcite deposition; it is less diverse today and was the most sensitive to ocean acidification. Corallinales were also reduced in cover and diversity but several species survived at high p CO2 ; it is the most recent order of coralline algae and originated when ocean chemistry favoured aragonite and high Mg calcite deposition. The sharp decline in cover and thickness of coralline algal carbonate deposits at high p CO2 highlighted their lower fitness in response to ocean acidification. Reductions in CO2 emissions are needed to limit the risk of losing coralline algal diversity. Abstract : We show for the first time that ocean acidification can cause a decline in the biodiversity of coralline algae. We reveal an exceedingly high level of cryptic diversity in the Japanese coralline algal flora and show that the effects of ocean acidification on coralline algal diversity worldwide have previously been underestimated. It is now clear that identification using molecular systematics tools significantly advances insights into the responses of marine communities to global change.